The Impact of Taxes and Transfers on Job Search - Gottschalk, Peter (Journal of Labor Economics, 1988)
This article develops a framework for analyzing the impact of taxes and transfers on the length of time a person waits to accept a job while receiving transfer payments. It considers the impact of changes in the parameters of a generic tax-transfer system characterized by a guarantee and a tax rate on the costs and benefits of search. The analytical results indicate that increases in guarantees need not increase duration of unemployment-the results for unemployment insurance are a special case of the more general formulation developed in this article. In fact, increases in guarantees and increases in tax rates may shorten the duration of unemployment while decreasing the labor supply of transfer recipients.